Pyrrole–Aminopyrimidine Ensembles: Cycloaddition of Guanidine to Acylethynylpyrroles - Olga V. Petrova (Molecules, 2021)
An efficient method for the synthesis of pharmaceutically prospective pyrrole–aminopyrimidine ensembles (in up to 91% yield) by the cyclocondensation of easily available acylethynylpyrroles with guanidine nitrate has been developed. The reaction proceeds under heating (110–115 °C, 4 h) in the KOH/DMSO system. In the case of 2-benzoylethynylpyrrole, the unexpected addition of the formed pyrrole–aminopyrimidine as N- (NH moiety of the pyrrole ring) and C- (CH of aminopyrimidine) nucleophiles to the triple bond is observed.